Supervisi Kepala Sekolah terhadap Kinerja Guru dalam Meningkatkan Pembelajaran Pendidikan Agama Islam : Studi di MTs. Darul Ulum Matang Danau Kecamatan Paloh - Anisa Trirezeki; Nuraini Nuraini; Alkadri Alkadri (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
This research is motivated by the phenomenon of principals implementing educational supervision of Islamic Religious Education teachers, this is done to improve the performance of Islamic Religious Education teachers at MTs. Darul Ulum Matang Danau, Paloh District. The focus of this research is: 1) How is the implementation of principal supervision of teacher performance in improving learning at MTs Darul Ulum Matang Danau?. 2) What are the results of the implementation of Principal supervision of Teacher performance in improving learning at MTs Darul Ulum Matang Danau? 3) What are the Supporting and Inhibiting Factors of Principal supervision of teacher performance in improving learning at MTs Darul Ulum Matang Danau? This research uses a qualitative approach with a phenomenological research type. Primary data sources in the research, namely: Principal and Islamic Religious Education Teacher at MTs Darul Ulum Matang Danau, Paloh District. Data collection uses three techniques, namely: observation, interview, and documentation techniques. The stages of data analysis start from data collection, data reduction, data display and data verification (drawing conclusions). The data validity checking techniques used were triangulation and member checking. The results of this study are: 1) The implementation of principal supervision at MTs Darul Ulum Matang Danau in improving Islamic Religious Education (PAI) teacher performance is carried out in the following ways: First, by conducting supervision or monitoring. Second, by assessing teacher performance and student understanding levels during learning. 2) The results of the principal supervision at MTs Darul Ulum Matang Danau in improving Islamic Religious Education (PAI) teacher performance have a significant impact on improving teacher performance. 3) The implications of principal supervision at MTs Darul Ulum Matang Danau are improving teacher performance in Islamic Religious Education (PAI) learning by improving teacher competency in planning, implementing, and assessing learning, which impacts teaching quality and student achievement.